Gulf Exhibit at the World's Fair, A Century of Progress, Chicago, Ill.
At the Gulf Exhibit will be found the World's Largest Auto Cylinder, a reproduction of the World's Largest Auto Cylinder, a reproduction of the World's Largest Atmospheric Vacuum Still, the Airplane Motor that set the World's Endurance Record, and many other things of interest. Don't miss it!